The paradox between the numerically competent baby and the slow learning of two- to four-year-old children - Rodríguez, Cintia (2015)
Since the 1980s, numerous laboratory investigations have been arguing that infants are numerically competent. This work presents a critical review of this line of research. We propose that despite the repertoire of numerical abilities attributed to infants and the seemingly natural character of the very first numbers in the numerical series, the semiotic complexity of their use and comprehension poses a cognitive challenge that children undertake, motivated, supported and often guided by others. This challenge involves a high degree of semiotic organization of the material world as well as an ability to manage early sign systems, systems which children learn how to use during their first years of life and which form the platform on which numbers are based.